Association of haemoglobin levels in the first trimester and at 26–30 weeks with fetal and neonatal outcomes: a secondary analysis of the Global Network for Women's and Children's Health's ASPIRIN Trial. (12th April 2021) - Jessani, S; Saleem, S; Hoffman, MK; Goudar, SS; Derman, RJ; Moore, JL; Garces, A; Figueroa, L; Krebs, NF; Okitawutshu, J; Tshefu, A; Bose, CL; et al.
Abstract : Objective: Limited data are available from low‐ and middle‐income countries (LMICs) on the relationship of haemoglobin levels to adverse outcomes at different times during pregnancy. We evaluated the association of haemoglobin levels in nulliparous women at two times in pregnancy with pregnancy outcomes. Design: ASPIRIN Trial data were used to study the association between haemoglobin levels measured at 6 +0 –13 +6 weeks and 26 +0 –30 +0 weeks of gestation with fetal and neonatal outcomes. Setting: Obstetric care facilities in Pakistan, India, Kenya, Zambia, The Democratic Republic of the Congo and Guatemala. Population: A total of 11 976 pregnant women. Methods: Generalised linear models were used to obtain adjusted relative risks and 95% CI for adverse outcomes. Main outcome measures: Preterm birth, stillbirth, neonatal death, small for gestational age (SGA) and birthweight <2500 g. Results: The mean haemoglobin levels at 6 +0 –13 +6 weeks and at 26–30 weeks of gestation were 116 g/l (SD 17) and 107 g/l (SD 15), respectively. In general, pregnancy outcomes were better with increasing haemoglobin. At 6 +0 –13 +6 weeks of gestation, stillbirth, SGA and birthweight <2500 g, were significantly associated with haemoglobin of 70–89 g/l compared with haemoglobin of 110–129 g/l The relationships of adverse pregnancy outcomes with various haemoglobin levels were more marked at 26–30 weeks of gestation. Conclusions: Both lower and some higher haemoglobin concentrations are associated with adverse fetal and neonatal outcomes at 6 +0 –13 +6 weeks and at 26–30 weeks of gestation, although the relationship with low haemoglobin levels appears more consistent and generally stronger. Tweetable abstract: Both lower and some higher haemoglobin concentrations were associated with adverse fetal and neonatal outcomes at 6–13 weeks and 26–30 weeks of gestation. Tweetable abstract: Both lower and some higher haemoglobin concentrations were associated with adverse fetal and neonatal outcomes at 6–13 weeks and 26–30 weeks of gestation.